(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
This study was carried out to examine the effect of selected fruit peels on growth and yield of okra (Abelmoschus esculentus). 10g of ground fruit peels of banana, watermelon, pawpaw, pineapple, plantain, orange was applied to 7 kg of soil and left for 7 days before planting of okra seed. NPK (15:15:15) serves as positive control while groups without fertilizer served as negative control for the study. Each treatment was replicated five times in polythene bags used as pots and watered every three days. The setup was arranged in Completely Randomized Block Design (CRBD). Plant height and stem girth were measured while number of leaves were also counted from 1 to 8 Week After Planting. The numbers of days to 50% flowering, pod length and pod diameter were also recorded from 1 to 8 Week After Planting. Data pooled in this study were subjected to Analysis of variance (ANOVA) and means with statistically significant difference at p<0.05 were separated using Duncan Multiple Range Test. Generally, results across weeks showed statistically significant difference for plant height, number of leaves, stem girth, days to 50% flowering, number of fruit and pod length while only the diameters of fruits did not respond to different nutrient sources. Okra grown with banana and watermelon peels gave the best overall performance which indicates that they contained sufficient nutrients for optimum production of okra. This study clearly indicates that banana and watermelon fruit peels could be used singly or in combination to effectively boost yield of okra.